STUDY OF THE PROGRESS OF HEALTH CARE SYSTEM INFORMATION TECHNOLOGY IN INDONESIA - Ridha Maharani (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
The research objective is to study the progress of information technology in the health service system in Indonesia. The research method is a descriptive qualitative approach. The results of the research are that the existence of various programs to reduce various population problems should be of concern to all parties involved so that improvements in the quality of human resources continue to occur. Apart from that, the government should pay more attention to the policies and legislation that have been made for the welfare of the Indonesian people.